(untitled) (Journal of the College of Education for Women, 2024)
The current paper examines the violence in Philip Ridley’s Mercury Fur (2005) set in a futuristic post-apocalyptic world. Through a critical analysis of the text, the study shows how violence becomes a mechanism for survival and coping with trauma and how a culture saturated with violence affects the individuals who inhabit it. The world depicted in Mercury Fur is characterized by a multitude of horrifying acts, ranging from the slaughtering of animals in zoos to random beheadings and the abuse of children. The impact of such a world on the mental state of those forced to endure it is incredibly intricate, resulting in inevitable trauma. Morality becomes a scarce commodity, elusive and challenging to attain, as it ultimately boils down to the lengths one is willing to go to ensure the survival and preservation of oneself and one has cherished loved ones. In a world where torture has become normalized and the veracity of memory has been distorted beyond recognition, one is compelled to ponder whether a life fraught with such excruciating agony and suffering is truly worth living. By analyzing the portrayal of violence in Mercury Fur, this research contributes to a deeper understanding of the psychological and emotional aftermath of trauma in a post-apocalyptic context. It emphasizes the significance of Ridley’s play in discussing the complexities of human behavior and the enduring impact of trauma in extreme circumstances.